1993
DOI: 10.1044/jshr.3602.286
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Stutterers' and Nonstutterers' Short-Term Recall and Recognition Performance

Abstract: Longer rehearsal times presumably reduce the efficiency of rehearsal and, hence, of short-term recall. The present experiment examined the question as to whether the slower subvocalization rate of people who stutter is correlated with inferior short-term serial recall and recognition performance. Rate of overt articulation was taken as a measure of rehearsal time. Lists of four nonlexical CVC syllables were presented for short-term serial recall and for short-term recognition. Nineteen adults who stutter and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…This supposition is consistent with the findings and interpretation of Bosshardt (1993) with AWS. As previously mentioned, adults who participated in the Bosshardt study were asked, among other things, to read sets of four CVC syllables and, following an intervening task, reproduce the syllables in writing.…”
Section: Relationship Between Language Skills and Nonword Repetitionsupporting
confidence: 81%
See 1 more Smart Citation
“…This supposition is consistent with the findings and interpretation of Bosshardt (1993) with AWS. As previously mentioned, adults who participated in the Bosshardt study were asked, among other things, to read sets of four CVC syllables and, following an intervening task, reproduce the syllables in writing.…”
Section: Relationship Between Language Skills and Nonword Repetitionsupporting
confidence: 81%
“…In one such study, adults who stutter (AWS) and their fluent controls were asked to reproduce, in writing, sets of four CVC syllables following their presentation and an intervening task (Bosshardt, 1993). Findings revealed that AWS reproduced significantly fewer syllables in the correct position than their fluent counterparts.…”
Section: Memory Processes In Individuals Who Stuttermentioning
confidence: 99%
“…For example, AWS have also shown slower RTs on tasks requiring monitoring of phonological structure (such as judging whether stimuli rhyme) and lexical analysis (making semantic category judgments; Bosshardt, 1993Bosshardt, , 1994Weber-Fox, Spruill, Spencer, & Smith, 2008), as well as while monitoring for particular phonemes (Sasisekaran, De Nil, Smyth, & Johnson, 2006). Some of these effects are exacerbated under conditions of increased cognitive load (Weber-Fox et al, 2004) Weber-Fox and colleagues noted that the data to date are "consistent with the hypothesis that underlying neural processes mediating lexical access may operate atypically in adults who stutter in the absence of overt speech" (Weber-Fox et al, 2004, p. 1246.…”
Section: Lexical Processing In People Who Stuttermentioning
confidence: 99%
“…Or, it is also possible that the group difference in picture naming relates to processes that are involved in the building (and SO) of dependent variables (7) for persons who stutter and control speakers, univariate F-values (F) for group effect, including t\2, w2, the confidence intervals (Cl), and the percentage of subjects misclassified (PM) values, as well as step- and retrieval of the associations between the pictures and their verbal labels. Such a suggestion was made by Bosshardt (1993), who found impaired recall and recognition performance for persons who stutter in comparison with matched control speakers. In sum, the task effect on group differences in reaction time found in the present study may indicate subtle differences between persons who stutter and control speakers in higher order (linguistic or memory) processing of verbal stimuli (see also Rastatter & Dell, 1987).…”
Section: Reaction Time Datamentioning
confidence: 99%